Mise en abyme. L’esperienza espansa della moda nell’età della mixed reality - Vaccari, Alessandra; Franzo, Paolo; Tonucci, Giulia (ZoneModa Journal, 2020)
The article investigates the 21st-century fashion through the theoretical lens of the mise en abyme, focusing on the mixed reality as an extended panorama between physical and digital. Four case studies were chosen within the Italian context, deemed as a place of experimentation and interaction between digital innovation and manufacturing tradition. Those cases have developed projects in mixed reality during the months of social distancing imposed by Covid-19, with significant consequences on creative processes, production, distribution, communication and consumption of fashion. In this scenario, the article questions the expansion of fashion experience, the ongoing transformation of the digital object, the conception and perception of time and the idea of intimacy at the time of Covid.